Lung epithelial-endothelial-mesenchymal signaling network with hepatocyte growth factor as a hub is involved in bronchopulmonary dysplasia - Sang, Yating; Qiao, Lina (Frontiers in Cell and Developmental Biology, 2024)
Abstract：Bronchopulmonary dysplasia (BPD) is fundamentally characterized by the arrest of lung development and abnormal repair mechanisms, which result in impaired development of the alveoli and microvasculature. Hepatocyte growth factor (HGF), secreted by pulmonary mesenchymal and endothelial cells, plays a pivotal role in the promotion of epithelial and endothelial cell proliferation, branching morphogenesis, angiogenesis, and alveolarization. HGF exerts its beneficial effects on pulmonary vascular development and alveolar simplification primarily through two pivotal pathways: the stimulation of neovascularization, thereby enriching the pulmonary microvascular network, and the inhibition of the epithelial-mesenchymal transition (EMT), which is crucial for maintaining the integrity of the alveolar structure. We discuss HGF and its receptor c-Met, interact with various growth factors throughout the process of lung development and BPD, and form a signaling network with HGF as a hub, which plays the pivotal role in orchestrating and integrating epithelial, endothelial and mesenchymal.